2006 European Microwave Conference 2006
DOI: 10.1109/eumc.2006.281456
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Electromagnetic Wave Propagation in Seawater

Abstract: It is often preferable to avoid using divers to undertake sub-sea activities, the alternatives being autonomous or remotely operated robotic vehicles and manipulators. This will only be achievable if robust communications can be established through seawater. Presently for such sub-sea activities it is necessary to use acoustic modems, which are only capable of operating with data rates of up to 50kbs -1 . Optical sensors can also be used but these rely on clear water and in many sea conditions propagation beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 3 publications
2
37
0
1
Order By: Relevance
“…According to table 1, attenuation in seawater at 2.4GHz is very high but propagation is feasible in its lowest frequency band (ISM subject to local acceptance) at 6.7 MHz. This theoretical value is in accord with fellow researchers' experiments results [6]. Although propagation of EM waves in seawater is more affected by attenuation in the near field, it depends on the launching technique.…”
Section: Em Wave Propagation Underwatersupporting
confidence: 90%
See 1 more Smart Citation
“…According to table 1, attenuation in seawater at 2.4GHz is very high but propagation is feasible in its lowest frequency band (ISM subject to local acceptance) at 6.7 MHz. This theoretical value is in accord with fellow researchers' experiments results [6]. Although propagation of EM waves in seawater is more affected by attenuation in the near field, it depends on the launching technique.…”
Section: Em Wave Propagation Underwatersupporting
confidence: 90%
“…In seawater, conductivity is approximately 4S/m whereas for freshwater it is in the mS/m range. Underwater communication research conducted at Liverpool John Moores University has shown that transmission at 5MHz frequency is feasible in seawater up to 90m giving a data rate of 500kbps that allows duplex video and data streams [6]. In [7], propagation at frequencies of 6 and 10.7MHz in a tank was also possible.…”
mentioning
confidence: 98%
“…[5] Since then, many researchers have determined the fields near the earth surface (or the seawater). Al-Shamma'a et al [6,7] and Siegel and King [8] investigated EM wave propagation in the seawater. MHz frequencies and loop antennas have been considered to present wave propagation characteristics in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, el principal problema del uso de RF es la alta atenuación que sufre en el ambiente acuático, especialmente en agua salada. Sin embargo, diferentes estudios (Zhang and Meng, 2012;Siegel and King, 1973;Shaw et al, 2006) y empresas como WFS (Wireless For Subsea) indican que, con las antenas necesarias, a frecuencias más bajas, y utilizando los mejores métodos de codificación y modulación, es posible establecer un enlace de comunicación hasta varias decenas de metros a través del agua (incluso en agua salada).…”
Section: El Dominio De La Intervención Robóticaunclassified